2014
DOI: 10.1080/07448481.2014.963107
|View full text |Cite
|
Sign up to set email alerts
|

University Students’ Knowledge and Attitudes Regarding Cervical Cancer, Human Papillomavirus, and Human Papillomavirus Vaccines in Turkey

Abstract: The results of the present study show that female university students have low levels of awareness and knowledge toward cervical cancer risk factors, HPV, and HPV vaccination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 44 publications
1
19
1
4
Order By: Relevance
“…Having children ranged from 2.5% to 8.5% in the university population. 3,8,[11][12][13][14][15][16][17][18] Other research corroborates the data of this investigation, noting that university students still lack knowledge about STIs. A study with university students from the health area of Rio de Janeiro city identified that 58.5% of the students do not know all forms of STIs transmission, although 48.5% said they had the whole knowledge.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Having children ranged from 2.5% to 8.5% in the university population. 3,8,[11][12][13][14][15][16][17][18] Other research corroborates the data of this investigation, noting that university students still lack knowledge about STIs. A study with university students from the health area of Rio de Janeiro city identified that 58.5% of the students do not know all forms of STIs transmission, although 48.5% said they had the whole knowledge.…”
Section: Discussionsupporting
confidence: 79%
“…13 This phenomenon was also observed in university students in Turkey, where only 10% of the interviewees recognized that HPV is a risk factor for cervical cancer and that 90% 9% did not know how to protect themselves from HPV. 14 In Portuguese research with university students in exchange, it was observed that 21% of participants did not know that STIs could be transmitted via oral sex. 15 Studies with African university students have pointed out that universal awareness about HIV/AIDS does not imply knowledge and that misinformation, misunderstanding and doubts are still present in popular knowledge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results show that not having been vaccinated against HPV was associated with lower levels of knowledge. Other studies have found low HPV vaccination rates among medical students was related to lack of knowledge about vaccine safety and efficacy, religious and cultural issues, and lack of government programs that cover the age range of students [28][29][30][31]. In addition, vaccination rates are higher in countries with national HPV vaccination programs [3].…”
Section: Discussionmentioning
confidence: 98%
“…HPV, bir kişiden diğerine genital temas yoluyla, özellikle vajinal veya anal seks yoluyla bulaşır. 28,29 Serviks kanseri riski bilgisi ve eğitimi, hastalığın tanı ve tedavisinde çok önemlidir. Bu bağlamda, özellikle sağlık çalışanlarına büyük sorumluluk düşmektedir.…”
Section: Hpv Enfeksiyonu Ve Aşılama Ile İlgili Bilgi Ve Tutumlarunclassified